DIDACTIC CONDITIONS OF ACTIVATION OF INDEPENDENT EDUCATION OF STUDENTS AND METHODOLOGY OF ORGANIZATION - Khayitova Sh.D (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
It is essential to take a separate approach to the organization of independent learning activities of students, where the individual approach is often carried out on a selective basis through the content of the proposed tasks. In this article, the author discusses how to increase the effectiveness of education through the independent learning of students in higher education today, the development of their cognitive abilities.